2017
DOI: 10.1002/jbmr.3155
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of NF1 in Osteocytes Increases FGF23 and Osteoid With Osteomalacia-like Bone Phenotype

Abstract: Neurofibromatosis type 1 (NF1, OMIM 162200), caused by NF1 gene mutations, exhibits multi-system abnormalities, including skeletal deformities in humans. Osteocytes play critical roles in controlling bone modeling and remodeling. However, the role of neurofibromin, the protein product of the NF1 gene, in osteocytes is largely unknown. This study investigated the role of neurofibromin in osteocytes by disrupting Nf1 under the Dmp1-promoter. The conditional knockout (Nf1 cKO) mice displayed serum profile of a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…This is important to notice because the progressive and long-term nature of tibia bowing and non-union in NF1, and data from genetic mouse models related to this condition, all support the idea that the cell of origin for this condition is a proliferating, undifferentiated mesenchymal progenitor, prior to the expression of Col2 and Osx [10,11]. Hence, the traits and behavior of Nf1 -deficient undifferentiated osteoprogenitors are likely to be more clinically relevant than the characteristics of Nf1 -deficient mature osteoblasts or osteocytes for instance [60], that are unlikely to be ever generated based on the defective differentiation of Nf1 -deficient osteoprogenitors.…”
Section: Discussionmentioning
confidence: 99%
“…This is important to notice because the progressive and long-term nature of tibia bowing and non-union in NF1, and data from genetic mouse models related to this condition, all support the idea that the cell of origin for this condition is a proliferating, undifferentiated mesenchymal progenitor, prior to the expression of Col2 and Osx [10,11]. Hence, the traits and behavior of Nf1 -deficient undifferentiated osteoprogenitors are likely to be more clinically relevant than the characteristics of Nf1 -deficient mature osteoblasts or osteocytes for instance [60], that are unlikely to be ever generated based on the defective differentiation of Nf1 -deficient osteoprogenitors.…”
Section: Discussionmentioning
confidence: 99%
“…MEKK2 deficiency rescues NF1-associated skeletal phenotypes. Previously, Nf1 fl/fl ;Dmp1-Cre mice have been reported as a model of skeletal NF1, finding that they display spontaneous fractures, accompanied by reduced mechanical strength, low bone mineral density, and high cortical porosity with an osteomalacia-like bone phenotype 25 . Use of the Dmp1-Cre here has the advantage that it avoids the severe growth and joint dysplasia phenotypes associated with the deletion of NF1 in early osteoprogenitors/skeletal stem cells as seen with Prx1 or Col2-Cre, which may complicate interpretation of genetic or pharmacologic rescue experiments 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…A second limitation is that the possibility of increased production of FGF23 from osteocytes cannot be denied. Kamiya et al reported that serum FGF23 levels showed a four-fold increase in NF1 conditional knockout mice (cKO) compared with age-matched controls, and immunohistochemistry showed significantly increased FGF23 protein in the cKO bones [29]. Further evaluations about this should be conducted in future.…”
Section: Discussionmentioning
confidence: 97%